Rancang Bangun Media Pembelajaran Mengenai Alat Musik Tradisional Jawa Berbasis Macromedia Flash Dengan Menggunakan Metode Computer Based Instruction Dan Multimedia Development Life Cycle - Rasyid, Adji Abdur; Harahap, Herlina; Siregar, Yunita Sari (Universitas Islam Negeri Sumatera Utara, 2022)
A musical instrument is an instrument that is made or modified with the aim of producing a sound or sound that produces a rhythm. Every region in Indonesia must have traditional musical instruments. One of them is a traditional Javanese musical instrument, which consists of Central Java, West Java, and East Java. With the help of information technology and programming languages, especially animations, there will be many benefits. One example is the application of learning media animation. With these benefits, a research is conducted that can help teachers and students by adopting technological advances. The selection of the program in writing this research is to use the macromedia flash application by applying the CBI (Computer Based Instruction) method and the MDLC (Multitimedia Development Life Cycle) method. The results of this study will display a visual animation in the form of a learning media application so that it can increase students' interest in learning about traditional musical instrument material and make students no longer find it difficult to understand the subject matter of traditional musical instruments. Keywords: Traditional Musical Instruments, Macromedia Flash, CBI, MDLC